PRE-HARVEST BIOMARKERS FOR IMPROVED STORABILITY AND PROCESSING QUALITY OF POTATOES UNDER HEAP STORAGE - Mehta, Ashiv (Potato Journal, 2016)
An improved heap storage technology with the use of CIPC (isopropyl N-(3-chlorophenyl) carbamate) has been developed for short-term storage of potatoes. Effect of tuber maturity and curing of skin on storage losses and processing quality was studied in three potato cultivars harvested at two maturity dates direct/after a curing period of 15 days following dehaulming of the crop to standardize pre-harvest factors to minimize losses.  Potatoes from different treatments were stored with/without CIPC treatment @ 20 mg a.i./kg of tubers. Curing of potatoes reduced losses (physiological + rotting) in potatoes  compared to direct harvest at both maturity levels. CIPC treatment significantly reduced losses in potatoes compared to control (untreated) particularly in cured potatoes up to 105 days of storageProcessing quality was improved by maturity while curing of potatoes did not record much effect. Reducing sugar (RS) content was significantly higher in immature tubers of Kufri Jyoti  and Kufri Pukhraj.  While in Kufri Chipsona-1, RS content remained low (